Impact of processing and analysis methodology on thalamic susceptibility assessment in multiple sclerosis - Salman, Fahad; Bergsland, Niels; Dwyer, Michael G.; Reeves, Jack A.; Ramesh, Abhisri; Jakimovski, Dejan; Weinstock-Guttman, Bianca; Zivadinov, Robert; Schweser, Ferdinand (PloS one, 2025)
Studies using quantitative susceptibility mapping (QSM) to investigate thalamic iron levels in people with multiple sclerosis (pwMS) have yielded inconsistent results. It has been speculated that cohort differences are responsible for these inconsistencies, leading to the phenomenological "early-rise late-decline" hypothesis, which posits that cohort age differences explain conflicting thalamic susceptibility findings. In a recent replication study, the authors failed to reproduce elevated thalamic susceptibility in pwMS previously reported by one of the only two QSM-based studies, despite matching cohort characteristics and processing, weakening the support for the phenomenological hypothesis. To investigate if the outcome of the recent replication study is robust with respect to different QSM algorithms and analysis methodologies. Using the same MRI dataset as the previous replication study, we assessed thalamic susceptibility across 83 pwMS and 44 healthy controls. To comprehensively evaluate methodological variability, we tested combinations of three background field removal (BFR) algorithms using various regularization parameters, four dipole inversion algorithms, three reference regions, and two segmentation methods. Each unique combination of a BFR algorithm (with its specific parameter) and a dipole inversion algorithm constituted a distinct pipeline, yielding a total of 19,558 susceptibility maps across 154 different pipelines. Thalamic susceptibility was lower in pwMS compared to controls independent of the chosen methodology, with differences in effect sizes primarily driven by the background field removal algorithms and their regularization parameters, reference region, and segmentation method. The impact of dipole inversion algorithms was minimal. Our study suggests high reproducibility of group-level clinical studies using QSM to study the thalamus in pwMS. In particular, methodological differences in processing and analysis are unlikely to explain contradicting findings of thalamic susceptibility in MS.